Superconducting properties of lithographic lead break junctions. (21st December 2017) - Weber, David; Scheer, Elke
Abstract: We have fabricated mechanically controlled break junction samples made of lead (Pb) by means of state-of-the-art nanofabrication methods: electron beam lithography and physical vapour deposition. The electrical and magnetic properties were characterized in a 3 He cryostat and showed a hard superconducting gap. Temperature and magnetic field dependence of tunnel contacts were compared and quantitatively described by including either thermal broadening of the density of states or pair breaking in the framework of a Skalski model, respectively. We show point contact spectra of few-atom contacts and present tunneling spectra exhibiting a superconducting double-gap structure.